Stratifikasi dalam praktek komunikasi bahasa Jawa dan masa depan kontekstualisasi kajian barat terhadap “orang Jawa” (Sebuah agenda riset) - Sarwono, Billy K. (Institute for Advanced Science, Social, and Sustainable Future, 2024)
The development of locally-based communication theories in Indonesia in the context of globalization and the advancement of communication technology. Communication experts in Indonesia feel the need to develop communication concepts that are in line with the local context. This concept has been pioneered by several communication experts in Asian countries such as China, India, Korea, and Japan. The dominance of Western theories has sparked a desire to research and develop communication science concepts by emphasizing cultural uniqueness. This research outlines the cultural characteristic differences between the West and the East, especially in left (West) and right (East) thinking, as well as the use of time. An analysis is conducted on the stratified Javanese language concept, including the use of different language levels according to social stratification. In this context, the research also associates post-structuralist and post-colonial concepts to understand the dynamics of communication in Javanese society. The research concludes with a discussion of the influence of moral systems, social stratification, and power in the communication process using the Javanese language. It is concluded that communication in Javanese society is not only influenced by language levels but also by ethical and moral systems that regulate relationships between social classes. This research aims to provide new insights into the communication system in Javanese society and stimulate further research in the field of related communication sciences.